Evaluasi Kematangan Manajemen Proyek Perangkat Lunak: Studi Kasus Pengajuan Tunggal Pengembangan Kepabeanan Karantina di Badan National Single Window Indonesia - Jeffry Adityapriatama; Dana Indra Sensuse (AI Society & STMIK Indonesia, 2024)
This investigation provides a critical assessment of the governance practices in project management within the development of the Single Submission Quarantine Customs (SSM QC) system at the Indonesia National Single Window Agency (LNSW). Employing the Kerzner Project Management Maturity Model (KPM3), the study meticulously compares existing management operations against the established Project Management Body of Knowledge (PMBOK) standards. It uncovers pivotal governance deficiencies that hinder the maturation of project management processes. The research sheds light on the necessity for systematic improvements, particularly in areas of risk assessment, human resources, procurement, and quality control. Recommendations from this study advocate for the adoption of robust governance frameworks and strategic management enhancements. The implementation of these recommendations is projected to significantly uplift LNSW's strategic project alignment, operational efficiency, and overall effectiveness, marking a substantial advancement in the domain of software project management and setting a precedent for future research in this area.